MULTI-MODAL MRI AT 7T TO DETECT AND QUANTIFY MULTIPLE SCLEROSIS CORTICAL GREY MATTER PATHOLOGY. (29th November 2012) - Mougin, OE; Mistry, N; Papachatzaki, MM; Gowland, P; Evangelou, N; Schmierer, K
Abstract : Introduction: Multiple sclerosis (MS) affects the central nervous system white (WM) and grey matter (GM). Standard MRI techniques only reveal lesions in the WM (WML). High field MRI promises better detection and quantification of GM lesions (GML). We optimized multimodal 3D MRI acquired at 7T for GML detection. Methods: MRI was acquired using post mortem MS brain on an Achieva 7T MRI scanner. Sequences acquired included (i) T2*weighted 3D-TFE, (ii) T2-weighted (T2w), (iii) phase-sensitive inversion recovery (PSIR), (iv) magnetization transfer ratio (MTR) maps, (v) double inversion recovery (DIR) and (vi) quantitative T1, T2 and T2* maps. Lesions were classified as either purely cortical or mixed. Results: MRI parameters were successfully optimized for post mortem MS brain. Contrast-to-Noise-Ratio (CNR) for lesions was highest on T2w followed by T2*w MRI. There were 137 mixed and 111 purely cortical lesions GML. No subpial lesions were detected. Conclusion: Our results suggest T2w MRI is the best technique to detect cortical GML in post mortem MS brain at 7T. Our inability to detect subpial lesions may be due to (i) the limited sample size (ii) the lack of non-MS-brain for comparison or (iii) the need for pathological confirmation of the MRI findings. We will therefore increase our sample size, include control brain in our study, and explore pathological correlates of the MRI techniques used.